SOME UNIQUE HERBAL REMEDIES AGAINST ARTHRITIS AND RHEUMATISM FROM IMAMPUR GHAT AREAS IN AHMEDNAGAR DISTRICT (M.S.) INDIA - Punjaji*, Salave Ashok (Journal of Pharmaceutical Research and Opinion, 2014)
An extensive field surveys were arranged in Imampur Ghat areas to document the ethno-medicinal information regarding the use of wild and endemic ethno-flora against arthritis and rheumatism. The information presented here, is being collected from the local inhabitants through verbal interviews by an informal ways during the period from pre-monsoon of 2009 to the post-monsoon of 2011.The paper focuses on the ethno-medicinal uses of 20 plant species belonging to 17 families used for curing arthritis ad rheumatism among the local inhabitants in their routine life.